PERSEPSI ANGGOTA KELOMPOK TANI TERNAK TERHADAP INSEMINASI BUATAN PADA SAPI POTONG DI KABUPATEN SOPPENG, PROPINSI SULAWESI SELATAN - Sitti Nurani Sirajuddin; Muhammad Irfan Said; Sutomo Syawal (State Islamic University (UIN) Alauddin, 2014)
ABSTRACT. This study aims to determine perceptions of farmers towards artificial insemination in beef cattle in Soppeng, South Sulawesi Province. This study was conducted in May and June 2014 after the socialization and training of artificial insemination in cattle farmer group members in the District Latobaja Salokaraja, Soppeng. This type of research is descriptive. Retrieval of data using questionnaires and in-depth interviews. The population is farmers who followed the socialization and training of IB and sample are members of farmer group Latobaja. The results showed perceptions of farmer group members are good enough to artificial insemination in terms of knowledge, interest and assessment of the IB.